Fluorescence Turn‐on Synthetic Lipid Rafts on Supramolecular Sheets and Hierarchical Concanavalin A Assembly. Issue 7 (25th February 2019) - Kim, Yongju; Liu, Xin; Li, Huichang; Lee, Myongsoo
Abstract: Here we report fluorescence turn‐on synthetic lipid rafts by self‐assembly of a cationic distyrylanthracene derivative on a negatively‐charged sheet in an aqueous solution. First, the negatively‐charged 2D membrane structure is formed by lateral associations of aromatic rods with carboxylate groups. Then, the synthetic rafts are floated on the surface of the negatively‐charged sheets through electrostatic interactions. The fluorescence of the synthetic rafts is turned on due to the aggregation of the positively‐charged AIE dye on the sheets, facilitating monitoring of the formation of rafts. Concanavalin A (Con A) protein can load hierarchically onto the synthetic rafts at neutral pH to provide discrete Con A aggregates with a uniform size of ≈12 nm. The uniform aggregates of Con A on the synthetic rafts can stimulate Jurkat cells with enhanced efficiency, as compared with random‐sized aggregates of Con A. Abstract : Raft builders : Fluorescence turn‐on synthetic lipid rafts by self‐assembly of an AIE dye on supramolecular sheets in an aqueous solution are reported. The synthetic rafts are floated on the surface of the negatively‐charged assembled sheets through electrostatic interactions. Con A protein can load hierarchically onto the synthetic rafts to provide discrete Con A aggregates with a uniform size, which show an enhanced ability of Jurkat cell stimulation.